Ecological and evolutionary consequences of living in a defaunated world - Galetti, Mauro [UNESP]; Dirzo, Rodolfo (Elsevier, 2013)
Defaunation, the loss or population decline of medium and large native vertebrates represents a significant threat to the biodiversity of tropical ecosystems. Here we review the anthropogenic drivers of defaunation, provide a brief historical account of the development of this field, and analyze the types of biological consequences of this impact on the structure and functioning of tropical ecosystems. We identify how defaunation, operating at a variety of scales, from the plot to the global level, affects biological systems along a gradient of processes ranging from plant physiology (vegetative and reproductive performance) and animal behavior (movement, foraging and dietary patterns) in the immediate term; to plant population and community dynamics and structure leading to disruptions of ecosystem functioning (and thus degrading environmental services) in the short to medium term; to evolutionary changes (phenotypic changes and population genetic structure) in the long-term. We present such a synthesis as a preamble to a series of papers that provide a compilation of our current understanding of the impact and consequences of tropical defaunation. We close by identifying some of the most urgent needs and perspectives that warrant further study to improve our understanding of this field, as we confront the challenges of living in a defaunated world. © 2013 Elsevier Ltd.
Keywords: Defaunation; Extinction risk; Rainforest; Trophic cascades; anthropogenic effect; behavioral ecology; community dynamics; ecological impact; ecosystem function; ecosystem structure; environmental degradation; environmental gradient; environmental risk; evolution; extinction risk; native species; phenotype; plant community; population decline; rainforest; trophic cascade; tropical environment; vertebrate